2003
DOI: 10.1016/s0008-6363(03)00499-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of reactive oxygen species in cocaine-induced cardiac dysfunction

Abstract: These data indicate that cocaine administration induces early NADPH-driven O2-. release which may play an important role in the development and progression of the LV dysfunction observed after chronic cocaine abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 38 publications
7
49
0
Order By: Relevance
“…On the other hand, treatment with antioxidants could prevent cocaine-induced cardiac dysfunction. It is reported that ROS takes part in the progress of cardiomyopathy after cocaine abuse (48,49). A significant reduction was observed in SOD in opium-treated Syrian hamsters as compared to the control group.…”
Section: Superoxide Dismutase (Sod)mentioning
confidence: 90%
“…On the other hand, treatment with antioxidants could prevent cocaine-induced cardiac dysfunction. It is reported that ROS takes part in the progress of cardiomyopathy after cocaine abuse (48,49). A significant reduction was observed in SOD in opium-treated Syrian hamsters as compared to the control group.…”
Section: Superoxide Dismutase (Sod)mentioning
confidence: 90%
“…Myocardial tissue MDA, a lipid peroxidation product that reacts with thiobarbituric acid, was determined as previously described [10,11]. Tissue was weighed and homogenized in a ratio of 1 g to 10 ml of 1.15% KCl.…”
Section: Myocardial Malondialdehyde (Mda) Measurementmentioning
confidence: 99%
“…It has been discovered recently that cocaine administration is associated with severe oxidative stress in the heart (Moritz et al, 2003;Pacifici et al, 2003;Kovacic, 2005;Ren et al, 2006;Isabelle et al, 2007). Although there are several potential enzymatic sources of ROS existing in the heart, in an animal model of chronic cocaine administration, treatment with apocynin (an NADPH oxidase inhibitor) has been reported to be effective in reducing ROS generation and to restore the cardiac output, stroke volume, and fractional shortening, suggestive of the involvement of an NADPH oxidase (Isabelle et al, 2007).…”
mentioning
confidence: 99%